Ethnomedicinal Plants Used for Treatment of Urolithiasis in India: A Review - Beldar, Vishal G.; Sidat, Parin Salim; Jadhao, Manojkumar M. (Current Traditional Medicine, 2022)
Background: Kidney stone is the most commonly observed and painful disease of the urinary tract in human beings. Numerous intrinsic and extrinsic factors are responsible for the formation of kidney stones, for instance, age, sex, heredity (intrinsic factors), climate, diet, geography, mineral composition, and water intake (extrinsic factors). The kidney stones are categorized into calcium, struvite or magnesium ammonium phosphate, uric acid or urate, cystine, and other types of stones based on chemical composition and pathogenesis. Due to the multifactorial nature of kidney stone disease, the patient may need to rely on complex synthetic medication. However, in ancient Indian history, there are several pieces of evidence where natural resources such as plants were used to remediation this lethal disease. Objective: The present review attempts to provide exhaustive ethnomedicinal and ethnopharmacological information on medicinal plants used for kidney stones in India. Result: Hitherto, 258 ethnomedicinal plants from 90 different families reported using for kidney stone application. The majority of the plant species are associated with three important families: Asteraceae, Amaranthaceae, and Fabaceae. Most of the plants are from Andhra Pradesh (43 plants), followed by East Bengal (38), Jammu & Kashmir (36), Uttarakhand (31), Panjab (27), Mizoram (23), Karnataka (20), Maharashtra (20) and Assam (18). The commonly used plant parts for the herbal preparation are roots (21.22 %) followed by leaves/leaf (20.15 %), and sometimes complete plant (17.77 %) is used. The most commonly used method for the formulation is decoction (46.41 %) followed by powder (18.66 %) and then extracts (15.78 %) of different aerial and non-aerial parts of the plant. More than sixty ethnomedicinal plants assessed the in-vitro and in-vivo activities against the kidney stone. Conclusion: The present review epitomizes the ethnomedicinal information of medicinal plants used for kidney stones and pharmacological evidence for anti-urolithiasis activity. Most reported medicinal plants are not yet scientifically explored and need immediate attention before losing important species due to excessive deforestation for farming and industrial needs.
Keywords: ethnomedicinal plants